Increase the economic value of the jojoba (Simmondsia chinensis) yield using evaluation of distinctive clones grown under the Egyptian environmental conditions - Esmail, A. E. G.; Amira, K. G. A.; Adss, I. A. A. (International Journal of Agricultural Technology, 2016)
Jojoba (Simmondsia chinensis) is an industrial crop being grown in the arid and semiarid regions. Evaluation of ten jojoba clones that were selected from privet jojoba farm was studied to compare their growth parameters such as, tree volume, branch length (cm), branch diameter (mm), number of nodes forming branches, mean length for secondary branches per every branch, leaf area, chlorophyll (A and B), flowering date, flowering percentage, fruit set percentage and seed yield per plant (g). Moreover, seed samples were analyzed for oil content, protein content, minerals content and carbohydrates content. Finally comparing between the studied clones using the different of total protein band and Random Amplified Polymorphic DNA (RAPD) to determine genetic relationships among jojoba genotypes. All these parameters showed significant differences among the studied clones during both seasons except branch diameter (mm) and minerals percentage in the first season as the differences between clones were insignificant. It was observed that the maximum values corresponded to the economic parameters were recorded in clones EAI 1 and EAI 4 compared with the others. The study of the different of total protein bands showed the different of total protein bands in ten jojoba clones. Random amplified polymorphic DNA (RAPD) technique was used to investigate the patterns and distribution of genetic variability in studied clones. Cluster analysis was conducted to generate a dendrogram to elucidate the relationships among jojoba genotypes. The dendrogram data divided the jojoba genotypes into two main clusters. Genotypes EAI 1 and EAI 4 were found in the same sub-cluster using RAPD primers. These genotypes also had almost similar values for most traits such as the maximum values of seed yield per plant and seed oil content. It is concluded that jojoba plants in the natural habitat of Egypt belong to different genotypes.